The comparative accuracy of 8 commercial rapid immunochromatographic assays for the diagnosis of acute dengue virus infection. - Blacksell, S; Newton, P; Bell, D; Kelley, J; Mammen, M; Vaughn, D; Wuthiekanun, V; Sungkakum, A; Nisalak, A; Day, N (2006)
BACKGROUND: The serological diagnosis of acute dengue virus infection relies on the detection of dengue-specific immunoglobulin M (IgM) antibodies. Immunochromatographic tests are rapid diagnostic tests (RDTs) that can be performed at the bedside, but they have not been fully validated for diagnosis of dengue infection. METHODS: More than 20 RDTs for diagnosis of acute dengue infection are commercially available. Of these, 8 were selected for evaluation of performance by use of characterized dengue and nondengue serum specimens, and results were compared with those of a previously published dengue IgM/IgG enzyme-linked immunosorbent assay in conjunction with dengue virus serotyping by reverse-transcriptase polymerase chain reaction. RESULTS: Assay sensitivities were low, ranging from 6.4% (95% confidence interval [CI], 4.0%-9.7%) to 65.3% (95% CI, 59.9%-70.5%), and specificities ranged from 69.1% (95% CI, 61.4%-76.0%) to 100% (95% CI, 97.8%-100%). Of the 8 tests, only 2 had sensitivities of >50%, the level considered to be clinically useful, and, of these, 1 had relatively low specificity (69.1%). Samples collected early in the infection were less likely to test positive than those collected later. A thermal stability study demonstrated a loss in performance of some RDTs when they were stored at a high ambient temperature for 3 months. CONCLUSIONS: Users of RDTs for dengue should be aware that many of these tests have a diagnostic accuracy that falls well below the manufacturers' claims. If an acute specimen yields a negative result, a convalescent serum sample should be tested to confirm the result. No RDT adequately differentiated primary and secondary dengue infections, and the tests should not be used for this purpose.